2020
DOI: 10.1002/pmrj.12497
|View full text |Cite
|
Sign up to set email alerts
|

Knee Flexion Contractures Are Associated with Worse Pain, Stiffness, and Function in Patients with Knee Osteoarthritis: Data from the Osteoarthritis Initiative

Abstract: Background Patients with or at risk of developing knee osteoarthritis (OA) can acquire a knee flexion contracture (FC). The prevalence, severity, and association of knee FC on OA outcomes such as pain, stiffness, and function are not well described and clinical scales may omit measuring joint range of motion. Objective (1) To determine if the presence and severity of a knee FC was associated with worse joint pain, stiffness and/or function and (2) to determine if this association was present in participants wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…4,65,80 Our findings are consistent with previous work showing an association between knee ROM and function in the OA joint. 11,12,14 The findings in this review are clinically relevant. Necessary joint ROM is often described in terms of thresholds for normal function, for example 90° of knee flexion for sitting, 40 94° for climbing stairs, 60 and 60° for normal ambulation.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…4,65,80 Our findings are consistent with previous work showing an association between knee ROM and function in the OA joint. 11,12,14 The findings in this review are clinically relevant. Necessary joint ROM is often described in terms of thresholds for normal function, for example 90° of knee flexion for sitting, 40 94° for climbing stairs, 60 and 60° for normal ambulation.…”
mentioning
confidence: 73%
“…4,65,80 Our findings are consistent with previous work showing an association between knee ROM and function in the OA joint. 11,12,14…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, patients with early-stage KOA have decreased axial tibial rotation excursion, while patients with end-stage KOA have increased knee adduction ( Nagano et al, 2012 ). Campbell et al (2020) found that knee flexion contractures are associated with worse pain, stiffness, and dysfunction in a severity-dependent manner in patients with KOA.…”
Section: Mechanisms and Symptoms Of Koamentioning
confidence: 93%
“…Among various factors that influence the clinical results, the range of motion (ROM) after TKA is a critical factor for patient satisfaction [21, 30, 31]. Flexion contracture is the common problem for postoperative knee, causing clinical symptoms [3, 5]. In TKA, surgeons aim to accomplish intraoperative full knee extension, whereas recurrence in flexion contracture is often experienced after TKA surgery even when surgeons confirm intraoperative full knee extension.…”
Section: Introductionmentioning
confidence: 99%